2010
DOI: 10.1021/bc100010k
|View full text |Cite
|
Sign up to set email alerts
|

Proton Sponge Trick for pH-Sensitive Disassembly of Polyethylenimine-Based siRNA Delivery Systems

Abstract: Small interfering RNAs offer novel opportunities to inhibit gene expression in a highly selective and efficient manner but depend on cytosolic translocation with synthetic delivery systems. The polyethylenimine (PEI) is widely used for plasmid DNA transfection. However, the water-soluble PEI does not form siRNA polyplexes stable enough in extracellular media for effective delivery. We previously showed that rendering PEI insoluble in physiological media, without modifying drastically its overall cationic charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 41 publications
1
107
0
Order By: Relevance
“…We anticipated that using PEI, microparticles would be found in the cytosol, because it has been previously reported that the capability of protonation of PEI results in the disruption of endosomes. [29][30][31] Authors that have covalently attached PEI to microparticles 20 have reported that these particles can be found free in the cytosol as early as 4-6 hours posttransfection when using PEI 70 KDa but not when using PEI 25 KDa. Kobayashi et al 21 demonstrated that the use of free cationic lipids increases the internalization of microparticles and that once in the endosomes compartment, they escape in a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipated that using PEI, microparticles would be found in the cytosol, because it has been previously reported that the capability of protonation of PEI results in the disruption of endosomes. [29][30][31] Authors that have covalently attached PEI to microparticles 20 have reported that these particles can be found free in the cytosol as early as 4-6 hours posttransfection when using PEI 70 KDa but not when using PEI 25 KDa. Kobayashi et al 21 demonstrated that the use of free cationic lipids increases the internalization of microparticles and that once in the endosomes compartment, they escape in a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric vectors that are effective for plasmid delivery often have to be modified in order to efficiently deliver siRNA. [39][40][41] In this case, the ternary block-statistical copolymer that showed highest gene transfer was also most effective at siRNA delivery without the need for additional modifications. The triblock copolymers in contrast display an insignificant silencing effect.…”
mentioning
confidence: 89%
“…When endocytosis of polyplexes was mediated by clathrin-dependent endocytosis, pDNA can escape the endosomal compartment and reach the cytosol by exploiting the protonation capacity of the polymers. In addition to the role played by their cationic groups in condensing pDNA, the polyplexes also carried acid-protonable groups such as secondary amines [101,102] or imidazole rings [103]. It is of note that when they route via the caveolea-dependent pathway, polyplexes can also reach the clathrin-dependent pathway [104].…”
Section: Overcoming Intracellular Barriersmentioning
confidence: 99%